(untitled) (Eventum: A Journal of Medieval Arts & Rituals, 2024)
This first article introduces the theme of the present special issue of Eventum that concerns the strong interrelationship between ritual and gender in medieval cultures. Drawing on contemporary ritual and gender theories, such as those of Catherine Bell, Judith Butler, Candace West and Don Zimmerman, and Erving Goffman, which highlight the key role of gender in ritual and treat ritual as the source of gender construction, the article explores briefly the gendered aspects of ritual and the ritual dimensions of gender in the Middle Ages while pointing out the shared characteristics of (medieval) ritual and gender. Followed by the special issue’s other contributions, this introductory article argues that a good understanding of medieval cultures’ workings cannot be achieved without taking into consideration the inevitable connections between ritual and gender.